(untitled) (Conferencea, 2021)
The article analyzes the state and development of the digital economy in developed countries. Economic growth in our country is the role of development and digital economy. It is compared with the experience of foreign countries. The Republic of Uzbekistan provides a number of direction for the development of for the implementation of the work done in the digital economy, the dependence of the economy on education and improving the quality of the education system, the introduction of new disciplines and a number of problems in new areas. Issues will be considered and suggestion will be made.